Improving Reading Skills Comprehension of Short Story Reading Material through the Skimming Method in Elementary School Students - Kamasiah; Karim Karim; Farisatma; Krisnawati (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
Improving Reading Comprehension Skills in Short Story Reading Material Through the Skimming Method for Class V Students of Elementary School State 1 Kaobula. Thesis, Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Buton. This research is a Classroom Action Research. Subjects of totaling 23 students. This research was conducted in two cycles, each consisting of four stages, namely planning, implementing, observing, and reflecting. How to improve reading comprehension skills on short story reading material through the skimming method of fifth grade students at Elementary School State 1 Kaobula? Purpose is improve reading comprehension skills on short story reading material through the skimming. Prior to using the skimming method,8 students (34.8%) completed grades with an average score of 50.61 and then experienced an increase in cycles I and II with 13 students completing grades. (56.5%) with an average value of 67.82. Cycle II with the acquisition of data on student scores that were completed as many as 19 students (82.6%) average value of 82.4. Skimming method can improve reading comprehension skills in short story reading material for fifth grade students of Elementary School State 1 Kaobula.